Identifying longitudinal growth trajectories of learning domains in problem-based learning: a latent growth curve modeling approach using SEM. - Wimmers, Paul F; Lee, Ming (Advances in Health Sciences Education, 2015)
To determine the direction and extent to which medical student scores (as observed by small-group tutors) on four problem-based-learning-related domains change over nine consecutive blocks during a two-year period (Domains: Problem Solving/Use of Information/Group Process/Professionalism). Latent growth curve modeling is used to analyze performance trajectories in each domain of two cohorts of 1st and 2nd year students (n = 296). Slopes of the growth trajectories show similar linear increments in the first three domains. Further analysis revealed relative strong individual variability in initial scores but not in their later increments. Professionalism, on the other hand, shows low variability and has very small, insignificant slope increments. In this study, we showed that the learning domains (Problem Solving, Use of Information, and Group Process) observed during PBL tutorials are not only related to each other but also develop cumulatively over time. Professionalism, in contrast to the other domains studied, is less affected by the curriculum suggesting that this represents a stable characteristic. The observation that the PBL tutorial has an equal benefit to all students is noteworthy and needs further investigation.